Analisis terhadap Keharmonisan Rumah Tangga Mursyid Suluk di Kabupaten Rokan Hulu Perspektif Hukum Keluarga Islam - Kurniawan, Anwar; Arisman (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
This research is motivated by the phenomenon of suluk (spiritual retreat) activities undertaken by mursyid (spiritual guides) in Rokan Hulu Regency, which demand intensive dedication to their disciples and thus have the potential to cause tension in family life. The focus of this study is the dynamics of family relations of suluk mursyid, the challenges faced by their spouses, and an Islamic family law perspective on the impact of suluk activities on household harmony. This research employs a descriptive qualitative method through a field study approach, using interviews as the primary data collection technique. The findings reveal role imbalances, lack of shared time, and emotional tension experienced by the mursyid’s wives. However, some mursyid are able to maintain family harmony through open communication and involving their wives in spiritual activities. From the perspective of Islamic family law, as reflected in the Compilation of Islamic Law (KHI) and Maqa>s}id al-Shari>’ah, the importance of maintaining balance (tawa>zun) between religious obligations and family responsibilities is emphasized. The practice of suluk is not justified if it causes harm (mad}arrah) or neglects family rights.